Formation of Optimal Portfolio Using A Single Index in Pharmaceutical Companies - Rosa, Sara Nurdia; Tereza, Ledia; Agustina, Efa; Desilfa, Yulana; Sari, Dian Puji Puspita (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The purpose of this study is to identify optimal portfolio stocks using the Single Index Model. This research applies a descriptive method with a quantitative approach. The population and sample consist of all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX), including: PT Merck Indonesia Tbk, PT Kalbe Farma Tbk, PT Tempo Scan Pacific Tbk, PT Darya Varia Laboratoria Tbk, PT Indofarma (Persero) Tbk, PT Kimia Farma Tbk, PT Pyridam Farma Tbk, PT Sido Muncul Tbk, and PT Pharos Tbk. The data used are secondary data obtained from sources such as www.idx.co.id, www.yahoofinance.co.id, and www.bi.go.id through documentation and literature review techniques. The results show that three companies—SIDO, PYFA, and DVLA—are considered optimal for portfolio formation, as their Excess Return to Beta (ERB) values are higher than the corresponding cut-off point (Ci).